Estudo teórico e computacional da estabilidade de fase cristalina e do mecanismo da ferroeletricidade da manganita hexagonal InMnO3 - Bispo, José Genário Alves (2019)
In this work it was performed a thorough theoretical study of structural, electronic and magnetic properties of the h-InMnO3 hexagonal manganite compound. As a computational tool it was employed the Full Potential Linearized Augmented Plane Wave electronic structure method, which is based on Density Functional Theory and implemented into the WIEN2k computer code. Exchange and correlation effects between the electrons were treated by the Generalized Gradient Approximation (GGA) functional, with addition of the Hubbard Ueff correction in order to correctly describe highly correlated Mn d-electrons. Three crystalline phases of the h-InMnO3 have been considered: the ferroelectric (FE) one (space group P63cm) and the two paraelectric (PE) ones (P3̅c and P63/mmc). The main objective was to verify which of these three phases exhibits the lowest energy when subjected either to ambient conditions or to compressive and tensile external pressures. In addition, it was performed an analysis of electronic origin of the FE distortion of the studied material. The results show that in the case of the h-InMnO3 with experimentally determined structural parameters (lattice constants, atomic positions) the P3̅c crystalline phase is energetically the most favourable. However, after performing the computational relaxation of these parameters, utilizing Ueff = 4,0 eV, the energies of the P63cm and P3̅c phases have been found equal and identified as the lowest ones. This conclusion changes when the material is subjected to external pressure. Under compressive strain the P63cm phase is found to be more energetically favourable than the P3̅c phase, while under tensile strain the P3̅c become easier to form. Comparative analysis of electronic structures of different phases revealed that a modification of the degree of hybridization between the In dz2- and apical Oap 2pz-states, going from the PE to the FE phase, could be the electronic origin for the FE distortion of the material. However, this should not be the unique mechanism for stabilization of the FE phase of the h-InMnO3 at sufficiently low temperatures, since the hybridization between the In 5s- and the O 2p-states should also be partially responsible for it.